2023
DOI: 10.3390/jcm12051743
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Outcomes of Patients with Severe SARS-CoV-2 Infection after Therapeutic Plasma Exchange by Number of TPE Sessions

Abstract: The high mortality risk in severe SARS-CoV-2 infections is tightly correlated to the extreme elevation of inflammatory markers. This acute accumulation of inflammatory proteins can be cleared using plasma exchange (TPE), commonly known as plasmapheresis, although the available data on performing TPE in COVID-19 patients is limited regarding the optimal treatment protocol. The purpose for this study was to examine the efficacy and outcomes of TPE based on different treatment methods. A thorough database search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Therefore, TPE is one of the therapies suggested for PIMS or severe SARS-CoV-2 infections when other therapeutic options fail. 14,20 The results of a meta-analysis indicated that TPE can reduce mortality in severe COVID-19 but with no change in ICU length of stay. 21 TPE has also been successfully used for the treatment of inflammatory syndromes after SARS-CoV-2-infections in adults and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, TPE is one of the therapies suggested for PIMS or severe SARS-CoV-2 infections when other therapeutic options fail. 14,20 The results of a meta-analysis indicated that TPE can reduce mortality in severe COVID-19 but with no change in ICU length of stay. 21 TPE has also been successfully used for the treatment of inflammatory syndromes after SARS-CoV-2-infections in adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…The basic aim of TPE is to eliminate cytokines, inflammatory proteins and pathological antibodies to reduce the complications and organ damage caused by a massive inflammatory mediated immune response. Therefore, TPE is one of the therapies suggested for PIMS or severe SARS-CoV-2 infections when other therapeutic options fail 14,20 . The results of a meta-analysis indicated that TPE can reduce mortality in severe COVID-19 but with no change in ICU length of stay 21 .…”
Section: Discussionmentioning
confidence: 99%